Multi-faceted regulation of CREB family transcription factors - Chowdhury, Md Arifur Rahman; Haq, Md Mazedul; Lee, Jeong Hwan; Jeong, Sangyun (Frontiers in Molecular Neuroscience, 2024)
cAMP response element-binding protein (CREB) is a ubiquitously expressed nuclear transcription factor, which can be constitutively activated regardless of external stimuli or be inducibly activated by external factors such as stressors, hormones, neurotransmitters, and growth factors. However, CREB controls diverse biological processes including cell growth, differentiation, proliferation, survival, apoptosis in a cell-type-specific manner. The diverse functions of CREB appear to be due to CREB-mediated differential gene expression that depends on cAMP response elements and multi-faceted regulation of CREB activity. Indeed, the transcriptional activity of CREB is controlled at several levels including alternative splicing, post-translational modification, dimerization, specific transcriptional co-activators, non-coding small RNAs, and epigenetic regulation. In this review, we present versatile regulatory modes of CREB family transcription factors and discuss their functional consequences.